POLA PEMBENTUKAN GOROAWASE DALAM BAHASA JEPANG - Tresnasari, Ningrum (IZUMI, 2017)
[Title: The formation of goroawase pattern in Japanese]Goroawase ( Japanese wordplay in number) is one of the phenomenon of language in japan.Goroawase can be defined as a language game that is widely used as a technique to memorize numbers or important numbers in Japan.This study aims to determine how the pattern formation of goroawase in Japanese. The method used in this research is descriptive qualitative method.Goroawase formed by means of use way read numbers in japanese to form a word which has a particular meaning. The formation of goroawase is divided into two types, there are derived from number into word and word into number. The formation of derived from numbers into a word generally used as a mnemonic ( memorizing techniques ) as in considering important years in Japan, mathematical formulas, and to remember the spesific of anniversary date.for example, the discovery of America , namely the year 1492 read as iyokuni. Goroawase which comes from the words into numbers is generally used as the making of a password , email address ( e-mail) or a private telephone number that can be customized with its own name or by words such desired aishiteru written words into 14 106 . gb777gb777slot gacorgb777gb777GB777GB777slot gacorslot gacor